Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1969
DOI: 10.1111/j.1365-2818.1969.tb00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative studies on the preservation of choline and ethanolamine phosphatides during tissue preparation for electron microscopy

Abstract: The loss of I4C-ethanolamine-and 3H-choline-labelled phospholipids from rat liver during preparation for electron microscopy by some less frequently used processing methods has been examined. Permanganate and formaldehydepotassium dichromate fixation followed by Araldite embedding were investigated and five procedures involving embedding in water-miscible methacrylates (GMA). These procedures included a conventional method of dehydration and embedding in GMA, a low-temperature GMA embedding method, dehydration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 35 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…Employing a chemical fixation procedure, we then found that lysozyme per se affected E. coli, resulting in disintegration of the cytoplasm, whilst the membranes still surrounded the cytoplasm even in severely damaged cells, leading to the formation of cell ghosts. Fixation with aldehydes with or without postfixation with osmium tetroxide results in severe changes, including loss of lipids (Cope and Williams, 1969), ondulation of the cell membranes, and aggregation of cytoplasmic components (Kellenberger, 1991). Loss of both cytoplasmic and membrane material can be assumed to be enhanced in cells undergoing degenerative changes.…”
Section: Discussionmentioning
confidence: 98%
“…Employing a chemical fixation procedure, we then found that lysozyme per se affected E. coli, resulting in disintegration of the cytoplasm, whilst the membranes still surrounded the cytoplasm even in severely damaged cells, leading to the formation of cell ghosts. Fixation with aldehydes with or without postfixation with osmium tetroxide results in severe changes, including loss of lipids (Cope and Williams, 1969), ondulation of the cell membranes, and aggregation of cytoplasmic components (Kellenberger, 1991). Loss of both cytoplasmic and membrane material can be assumed to be enhanced in cells undergoing degenerative changes.…”
Section: Discussionmentioning
confidence: 98%
“…Over the last decade, freeze-substitution has been used most frequently for the examination of eucaryotic systems (10,12,13); it has rarely been used on procaryotic cells. For this reason, it has been difficult to ascertain the power and scope of freeze-substitution as a technique for the preservation of microbial systems.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrastructural studies of fat droplets in NASH are useful because osmium tetroxide effectively preserves lipid-containing structures [32][33][34]. The fat droplet forms in or alongside the ER in conjunction with apolipoprotein B and adipophilin [35][36][37].…”
Section: Fat Dropletsmentioning
confidence: 99%